EMPOWERMENT OF SANTRIPRENEUR THROUGH E-COMMERCE STARTUP (Study of Modern Islamic Boarding School Datok Sulaiman, Palopo City) - M Wahyuddin Abdullah; Abdul Wahid Haddade; Ahmad Nouruzzaman (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
This research aims to develop empowerment with role model empowerment of santri through e-commerce startups embodying futuristic santripreneur in Pesantren Modern Datok Sulaiman Palopo. This field research study is classified in qualitative descriptive using phenomenological and participatory action research to produce information, knowledge, skills solve problems on research subjects, and apply actions in natural settings. The results of this study, the empowering process of santri was conducted together with teachers and board of santri PMDS Palopo through a new media called